Perlindungan Rahasia Dosa Peniten dalam Sakramen Tobat: Sebuah Tinjauan Kanonis - Suwito, Benny (Lux et Sal, 2023)
Catholic Church will always maintain the secret of the confession because confession is sacred and a priest has no right to reveal the contents of the confession to anyone. In order to understand properly why a priest cannot reveal the sins of the penitent or must protect the content of the confession, the writer is intended to review it through the lens of Canon Law and start by looking back at the meaning of Sacrament of Penance as the Church’s foundation to provide guarantees to penitents, even if they have serious sins such as sexual abuse. The writer expects that this article will open up an understanding that the confession of sins gets the right place so that the readers understand why priests must always keep the secret even if they would be punished for doing so.